Social norms and cultural services – community belief system and use of wildlife products in the Northern periphery of the Korup National Park, South-West Cameroon (2014)
In many traditional societies, beliefs and taboos influence human behaviour towards the natural environment. Such beliefs and taboos are informal institutions where norms rather than official laws determine land use and nature protection in general and wildlife in particular. The present study on beliefs and taboos of the people of the northern periphery of the Korup. National Park is an attempt to reveal how norms influence their relation to the environment. A total of 195 households were sampled through a household survey conducted in four villages. The results revealed that before the application of “modern” approaches for wildlife protection and management, the people relied on norms to establish a relationship with wildlife and nature. The enactment of the 1994 legislation on forest, wildlife and fisheries resulted in stiff resistance as it contradicts traditional norms. It was found that 57.4 % of the respondents still perceive wildlife as a resource that can never get extinct. Traditional norms had a differentiated impact especially on game protection. The study recommends that a wildlife benefiting code of beliefs and taboos is developed to provide a basis for establishing a synergy between park management laws and traditional belief/taboo systems that drive the management of wildlife